Large Lecture Halls: Whiteboards, Not Bored Students. Issue 7 (9th August 2018) - Reinholz, Daniel L.
Abstract: Large lecture halls are a common feature of many undergraduate mathematics programs. However, teaching effectively in a large lecture hall can be challenging. This paper discusses the use of personal whiteboards for students as a way to make large lecture halls a more productive learning environment. I discuss the logistics of using whiteboards, setting up norms, and provide examples of supporting instructional techniques. These techniques are: warmup problems, think-pair-share, group work, and student presentations. To support this exposition, I draw on personal reflections as an instructor and report from a brief student survey on their experiences using the whiteboards.